Systemic GDF11 replenishment ignites myocardial injury through diminishing anti-apoptotic activity of cardiac progenitor cells. (3rd October 2022) - Kraler, S; Vdovenko, D; Liberale, L; Camici, G G; Canestro, C D; Reiner, M; Carbone, F; Balbi, C; Vassalli, G; Mohammed, S A; Mach, F; Paneni, F; et al.
Abstract: Background: Tissue damage due to acute myocardial infarction is caused by both the ischemic insult and subsequent reperfusion injury (I/R). Restoration of coronary blood flow accelerates cardiomyocyte death, a phenomenon referred to as reperfusion injury, the extent of which is partly modulated by cardiac progenitor cells (CPC). Development of novel therapies to reduce infarct size, the main determinant of outcome, represent a huge unmet medical need (1). Systemic levels of growth differentiation factor 11 (GDF11), a TGF-β superfamily member that shares 90% homology with myostatin, decline with age, and GDF11 replenishment by heterochronic parabiosis or systemic recombinant GDF11 (rGDF11) delivery was postulated to have rejuvenating effects (2). Purpose: We aimed to probe the effects of systemic GDF11 replenishment on I/R injury and deepen insights into the molecular mechanisms involved. Methods: We designed a vehicle-controlled study in which young (3–4 months) and old (22–24 months) C57Bl/6 mice were randomly assigned to either daily systemic rGDF11 or control treatment over 30 days before myocardial I/R injury was induced. Dissected hearts were subjected to in-depth profiling followed by IPA-guided -omics to identify key regulatory mechanisms. Finally, in vitro experiments on human CPCs and HL-1 cardiomyocytes were performed. Results: Myocardial Gdf11 expression declined with age, whereas myostatin (Mstn) showed an opposing expression pattern (Fig. 1A), a trend similarly observed upon I/R (Fig. 1B). Surprisingly, after the 30-day study period (Fig. 1C), young and aged rGDF11-treated mice showed higher I/R-induced infarct size and serum cardiac troponin I levels than controls, despite comparable areas at risk (Fig. 1D). Importantly, while proxies of necroptosis/pyroptosis remained unchanged, rGDF11-treated animals showed reduced cardiomyocyte viability irrespective of their age (Fig. 2A). Targeted transcriptomics applied on cardiac tissues of both groups identified the CPC-marker Nkx2–5 to be differentially regulated (Fig. 2B-C), an expression pattern validated in an independent cohort at both mRNA and protein levels (Fig. 2D). In the adult myocardium, the expression of both Nkx2–5 and its cofactor Gata4 is mainly confined to CPCs; indeed, similar reductions in Nkx2–5 and Gata4 expression were observed in CPCs exposed to rGDF11 (Fig. 2E) which coincided with accelerated cardiomyocyte death if cultured in conditioned media obtained from CPCs treated with rGDF11 (Fig. 2F), pointing toward a paracrine signalling pathway. Conclusions: Myocardial expression of GDF11 declines with age, and is blunted upon I/R injury, thereby opposing the expression pattern of myostatin. Surprisingly, however, systemic GDF11 replenishment by rGDF11 supplementation enhances rather than reduces myocardial infarct size through augmented apoptosis, a phenomenon mediated by diminished cardioprotective function of CPCs. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Foundation for Cardiovascular Research – Zurich Heart House